(3bhd aj EjVGM GdhLg GdPi PcQ HWdjehS Cf Hg GSJNQGL ef JbOeg eSjQGJ GdbeQ GdOhQjg hgi GdeSJhjIs - (3KGHJ Hf bQI Hf RgQhf GdMQGfj GdUCHrj, CHh GdMSf,J (B288 (3g` s
(3ChdgG (B:s
(3cd ReGfjf eJSGhjjf aEf hGMO ef GdfjQjf EfeG JSJhi MQcJg GdMbjbI s
(3BNQgG (B:s
(3cGf eG jNQL gh eSjQ GdbeQ GdeSJhi ai GdWhd ai Gdjhe GdhGMO eYdhekG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B91 - (3U(B107s
(3fSNJg ef fSNI dCHi GdMSf KGHJ Hf bQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B98 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B101s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B385 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B81 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3Gdadcs